Pemberian Aromaterapi Lemon , Papermint dan Lavender untuk Menurunkan Frekuensi Mual & Muntah pada Ibu Hamil Trimester I: (Literature Review) - Anggun Sasmita; Desiska Pricilia Tumatar (Pusat Riset dan Inovasi Nasional, 2026)
Pregnancy is a physiological process that occurs in women, approximately 50% of women at the beginning of their pregnancy experience nausea and vomiting to varying degrees. Nausea and vomiting usually occur in the morning during early pregnancy or the first trimester, which is called morning sickness. There are many methods of treating nausea. and vomiting in pregnant women in the first trimester, both pharmacological and non-pharmacological. One non-pharmacological way is to use lemon, lavender and peppermint aromatherapy. This research method uses a literature review which includes a systematic search study of computerized databases (Google School and PubMed) taken within the last 5 years from 2019-2024. The articles obtained in the search were 12 journals, but after reviewing the articles and adjusting them to the titles, there were 5 journals. Conclusion: Lemon and peppermint aromatherapy have the same effectiveness in reducing nausea and vomiting in pregnant women, while lemon aromatherapy is more effective than lavender aromatherapy.